A Study of Writing Skills of Students at High Schools in Lahe of Naga Administrated Zone, Myanmar - Samvara; Kanokkamalade, Veerakam; Pintrymool, Narongchai (วารสารพุทธจิตวิทยา, 2026)
The study found that most Lahe high school students are male and aged between 16 and 20, and they face significant challenges in English writing. The main difficulties were vocabulary, grammar, and the writing process, while moderate problems were found in spelling, punctuation, and revising. Interviews with lecturers also confirmed these issues and added that students lack motivation and sufficient writing practice. To solve these problems, lecturers suggested focusing on grammar, vocabulary, spelling, and writing organization, while encouraging classroom practice, using technology, and providing motivation. Overall, the findings indicate that systematic practice and effective teaching strategies are essential for improving students’ English writing skills. This study investigates the critical challenges in English writing skills faced by high school students in Lahe, Naga-administered zone, Myanmar. Through questionnaires (N=70 students) and in-depth interviews with three lecturers, the research identifies grammar, vocabulary, planning/pre-writing, and drafting as key problem areas. Findings reveal moderate-to-high difficulty levels across all writing domains, with vocabulary (mean 3.80) and drafting (mean 3.55) posing the greatest hurdles. The study proposes actionable solutions, including enhanced grammar training, vocabulary building, technology integration, and process-focused pedagogy.